Modern methodology of designing a travel company in the Republic of Kazakhstan (Journal of Geography and Environmental Management, 2024)
Modern development of the tourism industry in the Republic of Kazakhstan is a rather active and intensive process, the main task of which is the gradual development of tourism in the country, corresponding to regional and international requirements of the tourism business and the provision of a full range of tourist services of different levels and directions. The purpose of the research, outlined in the article, was the process of formation of a modern methodology of designing a tourism company, based on the practical experience of the authors for more than ten years. The authors studied and analyzed the main regulatory and legislative documents that have a direct impact on the development of tourism in the country, as well as reports of leading tourism organizations of the country. Modern trends in the market of the service sector were studied, a large-scale survey of both the actors of the tourism industry and consumers of tourism services was conducted. The authors prepared a qualitative algorithm for creating a tourism company, which was the result of practical activity in the field of opening and successful management of tourism business from 2012 to the present. These studies, outlined in the article, will allow not only to form a qualitative idea of the current stage of tourism development in the Republic of Kazakhstan, but also give the opportunity to use the algorithm of opening a tourism company to build a successful tourism business in Europe.
Keywords: tourism, tourism company, tourism business, tourism services, tourism industry